Analisis Kebijakan Dividen Terhadap Pertumbuhan Dan Harga Saham Perusahaan - Munawar, Aang; Basyarewan, Ulvi Nursally (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
Financial management within a company must consider the welfare of the shareholders, in addition to the growth of the company must keep and maintain the viability of the company, management will be faced with the decision of the profit utilization. Two main alternatives to the use of profits are distributed as dividends or retained earnings. The decision is what is known as dividend policy, which determines how large a proportion of profits to be distributed as dividends. The purpose of this study is to determine the dividend policy, company,s growth and company's stock price on Sector Consumer Goods Indusfry with Sub. Sector Food and Beverages listed Stock Exchange of Indonesia and to determine the effect of dividend policy to the growth and stock price for 4 years, is during 2010 to 2013. This study proves that the partial dividend policy (X) had no significant effect on the growth of company (Y1), and dividend policy (X) had no significant effect on stock price of company(Y2) Key Words : Dividend Policy, Growth, Stock Price.